2017
DOI: 10.1016/j.appet.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Children's Eating Behavior Questionnaire in 3 year old children of a multi-ethnic Asian population: The GUSTO cohort study

Abstract: The Children's Eating Behaviour Questionnaire (CEBQ) was developed to measure eating behaviors related to obesity risk in children. However, this questionnaire has not been validated for use in South East Asia, where parenting practices are different from those in western countries and child obesity rates are increasing. The aim of this study was to examine the validity of the CEBQ administered to mothers of children aged 3 years in Singapore. Confirmatory factor analysis (CFA) was used to examine if the origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
44
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 25 publications
11
44
0
2
Order By: Relevance
“…As with other reported studies, the use of pressure to encourage a child to eat was not associated with any of the dietary intakes in our study[ 17 , 18 ], but only with lower BMI z -scores [ 14 ]. This feeding practice has also been associated with eating behaviours such as lower enjoyment of food [ 49 51 ], which has been shown in our own cohort study to be related to lower BMI z-scores [ 52 ].This suggests that maternal use of pressure might not have a direct impact on specific foods consumed by the children, but could still influence the overall calorie intake of the child. Like the practice of food restrictions, the use of pressure to eat may be a reaction driven by the mother’s perception that their child is not gaining enough weight[ 45 , 53 , 54 ], but without the intention of promoting intake or avoidance of specific food groups.…”
Section: Discussionmentioning
confidence: 99%
“…As with other reported studies, the use of pressure to encourage a child to eat was not associated with any of the dietary intakes in our study[ 17 , 18 ], but only with lower BMI z -scores [ 14 ]. This feeding practice has also been associated with eating behaviours such as lower enjoyment of food [ 49 51 ], which has been shown in our own cohort study to be related to lower BMI z-scores [ 52 ].This suggests that maternal use of pressure might not have a direct impact on specific foods consumed by the children, but could still influence the overall calorie intake of the child. Like the practice of food restrictions, the use of pressure to eat may be a reaction driven by the mother’s perception that their child is not gaining enough weight[ 45 , 53 , 54 ], but without the intention of promoting intake or avoidance of specific food groups.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores reflect slower eating pace, as perceived by the participating parent. The subscale showed a test‐retest reliability of r = 0.83 in the original study sample , was psychometrically supported in other validation studies , and had been used extensively with young children internationally.…”
Section: Methodsmentioning
confidence: 99%
“…However, subsequent validation studies in other Western countries and in Asian countries have shown mixed results, with some replicating the original subscales (Mallan et al, 2013; Domoff et al, 2015), while others could not (Sleddens et al, 2008; Santos et al, 2011; Svensson et al, 2011; Cao et al, 2012; Quah et al, 2017). For studies that have failed to replicate the original subscales, exploratory factor analysis (EFA) was used to generate revised subscales that were more culturally relevant to Western countries like Sweden (Svensson et al, 2011), the Netherlands (Sleddens et al, 2008), Chile (Santos et al, 2011), and to Asian countries such as China (Cao et al, 2012), and Singapore (Quah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%